PENGARUH DIGITAL MARKETING DAN ARTIFICIAL INTELLIGENCE TERHADAP PURCHASE DECISION MELALUI CUSTOMER SATISFACTION SEBAGAI MEDIASI - Serlyana, Riska Dara; Roosdhani, Mohamad Rifqy (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines how digital marketing and artificial intelligence (AI) influence consumer choices using customer satisfaction as a mediating variable. The study focuses on Glad2Glow, a local skincare product offered on Tokopedia. Using survey methods and quantitative methodology, SmartPLS 4.0 was used to assess data from 100 Generation Z respondents in Jepara Regency who had made online purchases. The results indicate that digital marketing and artificial intelligence (AI) increase customer satisfaction, which in turn significantly influences purchasing decisions. Furthermore, it is demonstrated that customer satisfaction acts as a mediator in the relationship between digital marketing and AI on purchasing decisions. This study offers theoretical additions to the digital marketing literature as well as practical applications for local brands and MSMEs leveraging digital tactics and AI technologies to improve consumer satisfaction and purchasing decisions.